Trichotillomania Comorbid with Schizophrenia - Othman, Zahiruddin; Fadzil, Nor Asyikin (Japan International Cultural Exchange Foundation, 2019)
Introduction: Trichotillomania (TTM) is now part of DSM-5 classification of obsessive-compulsive and related disorders. A quarter of schizophrenia patients suffer from obsessive-compulsive symptoms (OCS) and the use of atypical antipsychotics may worsen or even induce new onset OCS. Objective: A 25-year old man who presented with TTM comorbid with schizophrenia was studied. The symptomatology and treatment will be discussed. Results: The patient had prominent anxiety and mild OCS during the prodromal phase of schizophrenia. While on atypical antipsychotics treatments, he developed TTM which was partially reduced with addition of selective serotonin reuptake inhibitor (SSRI). Conclusion: Schizophrenia patient with prodromal OCS is probably at increased risk of developing TTM while on atypical antipsychotics treatment. Atypical antipsychotics and SSRI combination therapy is a useful strategy in such patient.